The Stability of Money Demand Function in Jordan: Evidence from the Autoregressive Distributed Lag Model - Saed, Adnan A.; Al-Shawaqfeh, Walid (International Journal of Economics and Financial Issues, 2017)
In this article, we attempt to examine the stability of real money demand function for the narrow and broad money (RM1, RM2) for the period 1995: Q1-2016: Q4 in Jordan using the autoregressive distributed lag (ARDL) cointegration framework. Besides the stability of real money demand, we investigate the potential long-run relationship between real demand for money and its determinants: real gross domestic product, real interest rate, stock price index and financial development index. Empirical results based on bounds testing procedure confirm that a long-run relationship exists between real monetary aggregates (RM1, RM2) and its determinants. Moreover, most of the official monetary aggregates were used for finding out the most stable monetary demand relationship, which could provide correct signals for monetary policy formulation; the study found that narrow monetary aggregate M1 was proper aggregate. In addition, the role of financial innovation in explaining the demand for money warrants attention in formulating monetary policy. The paper imply that the central bank is able to control narrow money RM1 more accurately than broader money RM2 and could effectively use RM1 as an instrument in formulating and conducting monetary policy. Keywords: Real money demand, ARDL Model, Monetary policy JEL Classifications: C01; C32; O42